Literasi Digital dalam Pendidikan Agama Islam : Studi Putaka Tantangan dan Strategi Implementasi di Era Media Sosial - Indri Herawati; Yan Fahmi Zuher; Sisri Anita (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2026)
The development of digital technology and social media has changed the way students obtain religious information, thus demanding the strengthening of digital literacy in Islamic Religious Education (PAI) learning. This study aims to analyze the challenges of implementing digital literacy in PAI learning and identify effective strategies to optimize its implementation. The novelty of the research lies in the integration of the concept of digital literacy with Islamic values, especially in the face of religious disinformation, the culture of instant information consumption, and digital ethics. This research uses the library research method by examining various journal articles and relevant scientific literature. The results of the study show that the implementation of digital literacy in PAI faces a number of challenges, such as the limited digital competence of teachers, the low critical thinking skills of students, the prevalence of unverified religious information, limited infrastructure, and weak understanding of digital ethics. Strategies that can be carried out include improving teachers' digital competence, integrating digital literacy in the PAI curriculum, strengthening the culture of tabayyun and critical thinking, digital ethics education based on Islamic values, and collaboration between schools, families, and the community. This strategy is expected to be able to form a generation of Muslims who are digitally capable and have noble character.